3.8k views
2 votes
Solve by elimination method 5x-2y=11, 3x+4y=4.​

2 Answers

6 votes

Answer:

x = 2 y= -1/2

Explanation:

5x-2y=11 {1} . 2

3x+4y=4 {2} . 1

-> 10x-4y=22

+ 3x+4y = 4

-> 13x = 26

-> x= 26/13 x= 2/1 x= 2

-> 3(2)+4y=4

->6+4y=4 -> 4y= 4-6

-> 4y= -2 -> y= -2/4 -> y=-1/2

User StarNamer
by
4.7k points
5 votes

★ How to do :-

Here, we are given with two equations. We are asked to find the value of x and y using substitution method. By using the first equation we will find the value of x by substituting the values. Then, we use the hint of x and then we can find the value of y. Then we can find the original value of x by using the value of y. Here, we also shift numbers from one hand side to the other which changes it's sign. So, let's solve!!


\:

➤ Solution :-


{\sf \leadsto 5x - 2y = 11 \: --- (i)}


{\sf \leadsto 3x + 4y = 4 \: --- (ii)}

First let's find the value of x by using first equation.


{\tt \leadsto 5x - 2y = 11}

Shift the number 2y from LHS to RHS, changing it's sign.


{\tt \leadsto 5x = 11 - 2y}

Shift the number 5 from LHS to RHS.


{\tt \leadsto x = (11 - 2y)/(5)}


\:

Now, let's find the value of y using the second equation.

Value of y :-


{\tt \leadsto 3x + 4y = 4}

Substitute the value of x.


{\tt \leadsto 3 \bigg( (11 - 2y)/(5) \bigg) + 4y = 4}

Multiply the number 3 with both numbers in brackets.


{\tt \leadsto (33 - 6y)/(5) + 4y = 4}

Convert the number 4y to like fraction and add it with the fraction.


{\tt \leadsto (33 - 6y + 20y)/(5) = 4}

Add the variable values on denominator.


{\tt \leadsto (33 + 14y)/(5) = 4}

Shift the number 5 from LHS to RHS.


{\tt \leadsto 33 + 14y = 5 * 4}

Multiply the values on RHS.


{\tt \leadsto 33 + 14y = 20}

Shift the number 33 from LHS to RHS, changing it's sign.


{\tt \leadsto 14y = 20 - 33}

Subtract the values on RHS.


{\tt \leadsto 14y = (-13)}

Shift the number 14 from LHS to RHS.


{\tt \leadsto y = ((-13))/(14)}


\:

Now, let's find the value of x by second equation.

Value of x :-


{\tt \leadsto 3x + 4y = 4}

Substitute the value of y.


{\tt \leadsto 3x + 4 \bigg( ((-13))/(14) \bigg) = 4}

Multiply the number 4 with the fraction in bracket.


{\tt \leadsto 3x + ((-52))/(14) = 4}

Shift the fraction on LHS to RHS, changing it's sign.


{\tt \leadsto 3x = 4 - ((-52))/(14)}

Convert the values on LHS to like fractions.


{\tt \leadsto 3x = (56)/(14) - ((-52))/(14)}

Subtract those fractions now.


{\tt \leadsto 3x = (108)/(14)}

Shift the number 3 from LHS to RHS.


{\tt \leadsto x = (108)/(14) / (3)/(1)}

Take the reciprocal of second fraction and multiply both fractions.


{\tt \leadsto x = (108)/(14) * (1)/(3)}

Write those fractions in lowest form by cancellation method.


{\tt \leadsto x = \frac{\cancel{108}}{14} * \frac{1}{\cancel{3}} = (36 * 1)/(14 * 1)}

Write the fraction in lowest form to get the answer.


{\tt \leadsto x = \cancel (36)/(14) = (18)/(7)}


\:


{\red{\underline{\boxed{\bf So, \: the \: value \: of \: x \: and \: y \: is (18)/(7) \: and \: ((-13))/(14) \: respectively.}}}}

User Nichols
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.